The ratio of dihomo-γ-linolenic acid to deoxycholic acid species is a potential biomarker for the metabolic abnormalities in obesity - Lei, Sha (FASEB J, 2017)
Bile acid (BA) signaling regulates fatty acid metabolism. BA dysregulation plays an important role in the development of metabolic disease. However, BAs in relation to fatty acids have not been fully investigated in obesity-related metabolic disorders. A targeted metabolomic measurement of serum BA and free fatty acid profiles was applied to sera of 381 individuals in 2 independent studies. The results showed that the ratio of dihomo-γ-linolenic acid (DGLA) to deoxycholic acid (DCA) species (DCAS) was significantly increased in obese individuals with type 2 diabetes (T2DM) from a case–control study and decreased in the remission group of obese subjects with T2DM after metabolic surgery. The changes were closely associated with their metabolic status. These results were consistently confirmed in both serum and liver of mice with diet-induced obesity, implying that such a metabolic alteration in circulation reflects changes occurring in the liver. In vitro studies of human liver L-02 cell lines under BA treatment revealed that DCA and its conjugated form, TDCA, significantly inhibited mRNA expression of fatty acid transport protein 5 in the presence of DGLA, which was involved in hepatocyte DGLA uptake. Thus, the DGLA:DCAS ratio may be a promising biomarker for metabolic abnormalities in obesity.—Lei, S., Huang, F., Zhao, A., Chen, T., Chen, W., Xie, G., Zheng, X., Zhang, Y., Yu, H., Zhang, P., Rajani, C., Bao, Y., Jia, W., Jia, W. The ratio of dihomo-γ-linolenic acid to deoxycholic acid species is a potential biomarker for the metabolic abnormalities in obesity.